2015
DOI: 10.3109/00016357.2014.949842
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial pain and symptoms of temporomandibular disorders in Finnish and Thai populations

Abstract: Results: After adjusting for age, gender and education, the logistic regression analysis showed that Thai subjects had an increased risk for reporting oral pain (OR 4.5, 95% CI 3.7-5.4), tooth pain (OR 2.0, 95% CI 1.8-2.4) and pain in the face (OR 1.5, 95% CI 1.2-1.7). Conclusions:It can be concluded that Thai people report more orofacial pain symptoms than Finnish subjects. Cross-cultural factors exist in the background of reporting pain symptoms in the oral and facial area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…However, based on previous results, the duration of the reference period (1 month vs 12 months) does not seem to have a statistically nor clinically significant effect on reported oral impacts [42]. A re-analysis of the same data on four singleitem questions was conducted, showing the agreement to be substantial for three items: facial pain, jaw pain and OHIP-14 pain item [43]. The re-analysis showed moderate agreement for the fourth item, dental pain, which is commonly acute compared to facial pain, which is more often chronic.…”
Section: Discussionmentioning
confidence: 97%
“…However, based on previous results, the duration of the reference period (1 month vs 12 months) does not seem to have a statistically nor clinically significant effect on reported oral impacts [42]. A re-analysis of the same data on four singleitem questions was conducted, showing the agreement to be substantial for three items: facial pain, jaw pain and OHIP-14 pain item [43]. The re-analysis showed moderate agreement for the fourth item, dental pain, which is commonly acute compared to facial pain, which is more often chronic.…”
Section: Discussionmentioning
confidence: 97%
“… 34 36 There are also cross-cultural differences in pain reporting; for example, Thai participants are more likely to report orofacial pain symptoms than Finnish participants. 37 Another study comparing the prevalence of TMD pain in Chinese and Swedish people found that the former reported higher prevalence. 38 Sensitivity to pain, as determined by quantitative sensory testing, is lower in White individuals than in non-Whites, corroborating the cross-cultural differences in orofacial pain prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…TMD is considered the major cause of non-dental pain in the orofacial region, and it negatively affects the quality of life (QoL). ( 12 - 14 ) Comprehensive measurements of TMD and its impact in life are commonly captured using QoL questionnaires.…”
Section: Introductionmentioning
confidence: 99%